História e literatura : identidade, ancestralidade e diáspora na obra Axés do Sangue e da Esperança (orikis) de Abdias Nascimento - Soares, Sandro Alves (2024)
This research has as its source the literary work of poems Axés do sangue e da esperança (orikis) (1983), by Abdias Nascimento (1914-2011). An analysis of poems (orikis) that make up the work was carried out, using them as a historical source to understand which elements are mobilized by the author to construct a possible black identity in Brazil. Abdias Nascimento uses a language linked to elements of Africanbased cosmologies, moving away from Western literary and artistic schools, demarcating an innovative and unique style that connects with the aesthetics and philosophies of Afro-diasporized peoples. The poems also present elements of the ancestry and history of the black population in Brazil, evoking the memory of women and men who resisted, rebelled against and fought against the slave society, racism and religious intolerance. These elements of Abdias Nascimento's work manifest themselves to compose a possible black identity that is approached here based on the interconnection between the author's life and the literary work.